Case report: a paroxysmal hemicrania responsive to verapamil - Cesar, Alcântara Ramos de Assis; Ferreira, Pablo Guarisco; Fabris, Ângelo Afonso; Silva, Paola Bernardi da (Headache Medicine, 2022)
Introduction Paroxysmal hemicrania (PH), a trigeminal autonomic headache, is characterized by unilateral pain in the orbital, supraorbital, and temporal regions, accompanied by nasal congestion and ocular hyperemia, with a predominance (not exclusively) in women, with attacks lasting 2 to 30 minutes and occurring several times daily. Pain crises have been known to cease completely or almost completely with the use of indomethacin. However, in some patients, the side effects caused by taking the drug prevent continuation of treatment. There is also the possibility of a partial response to the first-line drug. In these cases, alternative drugs are chosen, with verapamil being one of the drugs of choice. Objectives In this report, we present a case of a patient with a partial response to the first-line drug therapy and good responsiveness to verapamil. Methods We collected patient data through the electronic medical record. Afterward, we reviewed the literature regarding paroxysmal hemicrania and its responsiveness to indomethacin and verapamil. Results A 56-year-old woman presented with a 1-year history of throbbing pain in the left hemiface, and retro-orbital and temporal ipsilateral pain, lasting approximately 30 minutes with a frequency of 5-6 episodes per day and a maximum remission period of 3 months. The headache attacks were associated with nasal congestion and allodynia and had worsened recently. Her medical history was positive for major depressive disorder and hypertension. At the time she presented, she was taking carbamazepine 900 mg per day, which resulted in partial relief of pain. Clinical examination revealed pain on palpation of the trigeminal branches on the left side, bilateral temporomandibular pain, and pain on palpation of the right greater occipital nerve. Magnetic resonance angiography of the head showed no abnormalities... (Too see the complet abstract, please, check out PDF.)